Case Report: Septic shock due to Pasteurella multocida in an immunocompetent elderly from a rural area of the Colombian Caribbean (2023)
Pasteurella multocida is a germ known to present opportunistic pathologies in most cases associated with contact with animals or their secretions. Systemic infections are rare and tend to occur in patients with risk factors or those who have contact with animals. A case of P. multocida bacteremia is presented in a 76-year-old male patient from a rural area of the Colombian Caribbean who was admitted due to a neurological condition with no personal history and no relevant epidemiological data. His deterioration was torpid, and he died possibly from P. multocida.